LB1.1 Randomised controlled trial of a complex intervention to improve school-based hpv vaccination for adolescents: the hpv. edu study. (13th September 2015) - Skinner, SR; Davies, C; Cooper, S; Stoney, T; Marshall, H; Jones, J; Collins, J; Hutton, H; Parrella, A; Zimet, G; Regan, DG; Whyte, P; et al.
Abstract : Introduction: In the context of universal (male and female) school based HPV vaccination program, we evaluated a complex intervention to promote: 1) student knowledge about HPV vaccination; 2) psycho-social outcomes and 3) vaccination uptake. Methods: We recruited a stratified random sample of schools across two Australian states, and randomly allocated to intervention or control. The intervention included adolescent education; distraction/relaxation on vaccination day; a brochure and decisional support tool for adolescents and parents; and program logistical strategies, in addition to routine state based vaccination guidelines. Both intervention and control followed routine state based guidelines. We compared intervention and control with regard to: student questionnaire data pre-dose 1, 2, 3 on HPV knowledge, vaccination decisional involvement, vaccination self-efficacy, fear and anxiety, and vaccine uptake. Immunisation data collection was ongoing in 2015. Results: We recruited 21 intervention schools (3806 students) and 19 control (3159). Pre-dose 1 questionnaire student knowledge: 65% vs. 33% correct responses, (difference 32%; 95% CI: 27%, 36%); decisional involvement score: 3.7 vs. 3.6 (difference 0.11; 95% CI: 0.06, 0.16); self-efficacy score: 74 vs. 71 (difference 4; 95% CI 1, 7); fear/anxiety score: 2.6 vs. 2.7 (difference -0.11; 95% CI: -0.19, -0.02). At least one vaccine dose was given to 3277 (86.1%) students in intervention schools versus 2697 (85.4%) in control schools, difference 0.4% (95% CI: -2.6, 3.3). Conclusion: Our intervention significantly improved adolescent knowledge and psycho-social outcomes, but not HPV vaccination coverage, which was high in both groups, resulting in a possible ceiling effect. Disclosure of interest statement: This study was funded through a National Health and Medical Research Council Project Grant (1026765) and an investigator driven bioCSL research grant. SR. Skinner's institution has received honoraria for Advisory Board meetings and educational symposia from GSKbiologicals and Pfizer.